Plasmapheresis, Photopheresis, and Endovenous Immunoglobulin in Acute Antibody-mediated Rejection in Kidney Transplantation - Pretagostini, R.; Poli, L.; Gozzer, M.; Pettorini, L.; Garofalo, M.; Novelli, S.; Cinti, P.; Berloco, P.B. (Transplantation proceedings, 2015)
Acute antibody-mediated rejection (AAMR) is the subject of much research. It is diagnosed by C4d staining at biopsy and circulating donor-specific antibodies (DSA). The combination of intensive plasmapheresis and intravenous immunoglobulin (IVIG) has been recognized as an effective treatment for AAMR. We report our single-center experience on AAMR treatment. We treated 23 transplanted patients (group A) with protein-A immunoadsorption (IA) and 7 patients (group B) with double-filtration plasmapheresis. All patients were treated with IVIG (400 mg/kg/d). Basic immunosuppression included cyclosporine, steroids, azathioprine, and antilymphocyte globulin or monoclonal antibodies (OKT3). A subgroup of 3 patients (3/7; group B1) was treated with photopheresis. In both groups, the mean number of extracorporeal procedures was 7.3 ± 4.5 and 5.5, respectively; the mean duration of treatment was 12.3 ± 10.2 and 14.5 days, respectively. In group A, we observed negative cross-matching in 96% after mean of 18 days; 1 patient died from sepsis, and 6 lost their grafts. In group B, negative circulating DSA were observed in all patients after a mean of 25 days, and 1 patient lost their allograft. In our observation, the 2 extracorporeal procedures had similar effects in terms of graft survival, DSA removal, and cross-match negativity (group A 74% vs 86%; 95.6% vs 100%). IA was faster for DSA removal. In our opinion, the higher costs of IA suggests its use just in high-risk cases, such as in hyperimmune or sensitized patients. Further studies are necessary to improve our knowledge. •The combination of intensive plasmapheresis and IVIg has been recognized as an effective treatment for AAMR.•We report our single-center experience with AAMR treatment.•We compared treatment with IA and with DFPP.•IA revealed to be faster for DSA removal.